Characterization of Probiotic Properties of Lactic Acid Bacteria Isolated from Yoghurt Available in Bangladesh - Mohammad Shaokat Ali; Shamima Ahmed; Md. Forhad Uddin; Abdul Matin; Mohammad Sharif Uddin; Nilufa Yeasmin (Turkish Journal of Agriculture: Food Science and Technology)
Yoghurt is the common fermented dairy product consumed worldwide and it is considered a potential source of probiotic bacteria (Lactobacilli and Lactococci). To assess the in-vitro probiotic properties of lactic acid bacteria, Lactococcus lactis subsp. lactis, Lactobacillus delbrueckii and Lactobacillus plantarum species isolated from yoghurt sold in different local markets of Chittagong region in Bangladesh were examined by morphological characteristics and biochemical tests. In the preliminary test, all isolates were grown well at acidic pH (pH 3-5) while the optimum growth temperature was 37°C and better growth was observed in the presence of 1-8% NaCl concentrations. In addition, the selected isolates were able to survive up to 3% bile salt concentrations while the best tolerance was at 1% bile salt. The strains successfully inhibited the growth of common pathogenic bacteria likely Escherichia coli, Pseudomonas aeruginosa, Salmonella Paratyphi, Staphylococcus aureus and Bacillus subtilis examined by in vitro growth inhibition test. Most of the isolated strains exhibited resistance pattern against ten commonly used antibiotics in foodborne illness in the country. However, the strains in yoghurt sold at Chittagong city have ideal probiotic characteristics and this fermented dairy product could be a potential source of human probiotic bacteria.